2013
DOI: 10.1161/hypertensionaha.111.00469
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Sensitive Endoplasmic Reticulum Stress and Autophagy at Rostral Ventrolateral Medulla Contribute to Hypertension in Spontaneously Hypertensive Rats

Abstract: Abstract-Perturbations of proper functions of the endoplasmic reticulum (ER) cause accumulation of misfolded or unfolded proteins in the cell, creating a condition known as ER stress. Prolonged ER stress has been implicated in hypertension. Oxidative stress in the rostral ventrolateral medulla (RVLM), where sympathetic premotor neurons for the maintenance of vasomotor tone reside, plays a pivotal role in neurogenic hypertension. This study aimed to evaluate the contribution of ER stress in RVLM to oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 59 publications
(79 reference statements)
1
54
0
1
Order By: Relevance
“…rats given Ang II and treated with either tauroursodeoxycholic acid (TUDCA) or PBA led to a 20 mm Hg decrease in blood pressure with either inhibitor, compared with Ang II treatment alone. 55 The Ang II-treated rats receiving either TUDCA or PBA had normalized levels of serum creatinine, a characteristic of impaired renal function, suggesting an attenuation of renal dysfunction in these rats. 56 In our study, both UDCA and 4-PBA improved renal dysfunction and decreased blood pressure after treatment for 8 weeks.…”
Section: Discussionmentioning
confidence: 90%
“…rats given Ang II and treated with either tauroursodeoxycholic acid (TUDCA) or PBA led to a 20 mm Hg decrease in blood pressure with either inhibitor, compared with Ang II treatment alone. 55 The Ang II-treated rats receiving either TUDCA or PBA had normalized levels of serum creatinine, a characteristic of impaired renal function, suggesting an attenuation of renal dysfunction in these rats. 56 In our study, both UDCA and 4-PBA improved renal dysfunction and decreased blood pressure after treatment for 8 weeks.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, Western blot analysis revealed decreased levels of p-AMPK, and elevated levels of p-eIF2α, ATF3, ATF6, XBP1 and cyclooxygenase 2 (COX-2) in SHR carotid arteries. Chao et al [121] found that ERS promoted oxidative stress associated with hypertension in the rostral ventrolateral medulla (RVLM) by increasing the expression of GRP78 and p-eIF2α. ERS also promoted vasoconstriction.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%
“…Salubrinal currently has a new therapeutic value. Chao et al [121] reported that in the RVLM of spontaneously hypertensive rats, salubrinal-mediated ERS stability relieved hypertension. Furthermore, induction of oxidative stress by Ang II induced ERS in the RVLM; induction of ERS by tunicamycin in the RVLM induced the pressor response in normotensive Wistar-Kyoto rats.…”
Section: Endoplasmic Reticulum Stress Is Involved In the Development mentioning
confidence: 99%
“…ER stress has previously been implicated in hypertension (7,37). To determine whether brain ER stress contributes to DOCA-salt hypertension, and whether ACE2 blunts DOCA-salt hypertension through prevention of ER stress, we measured ER stress marker mRNA and protein levels in the SFO and PVN regions.…”
Section: Characterization Of Sl Transgenic Micementioning
confidence: 99%
“…ER stress has been implicated in neurodegenerative diseases, cancer, obesity, and diabetes (13). Very recently, ER stress has been suggested in the development and maintenance of neurogenic hypertension (7,37). However, the mechanisms involved remain to be determined.…”
mentioning
confidence: 99%